PERANAN KARANG TARUNA PANCASILA DALAM MEMBENTUK JIWA KEPEDULIAN SOSIAL PEMUDA DI DESA SUNGAI NYIRIH - Sisna Sisna; Rum Rosyid; Thomy Sastra Atmaja (Universitas Tanjungpura, 2021)
AbstrakThis study aims to determine the activities, the process of implementing activities, supporting and inhibiting factors, as well as the efforts of the Karang Taruna Pancasila organization in forming the spirit of social awareness of youth in Sungai Nyirih Village.The research method used is descriptive with a qualitative approach.The results of this study indicate that the Karang Taruna Pancasila activities in order to form the spirit of social awareness of the youth in Sungai Nyirih Village such as donations to the needy, fundraising, community service, and commemorating national holidays. The process of implementing the activities carried out in forming the spirit of social awareness of youth has been seen when they carried out several activities. The activities carried out are structured and unstructured, the permits are complete, and the members who participate in the activities all provide assistance sincerely, both materially and non-materially. In forming the spirit of social care, of course, there are supporting and inhibiting factors that are passed as well as the efforts made to address these obstacles.Keywords: Youth Organization, Social Awareness, Youth.